Salivary duct carcinoma: report of eight cases - Minamino, Masayuki; Tsuji, Hiroyuki; Adachi, Mani; Yamashita, Toshio; Iwai, Hiroshi; Akagi, Mari; Nagata, Motoki; Konishil, Masaya; Yukawa, Hisaya (JOURNAL OF JAPAN SOCIETY FOR HEAD AND NECK SURGERY, 2005)
Eight cases of salivary duct carcinoma in the parotid gland are reported. Neither fine-needle aspiration biopsy nor frozen section was an effective tool for diagnosis before or during surgery. Radiation therapy and/or chemotherapy did not show preventive effects on cancer relapse. Although surgical operation was performed for all eight cases, only three were cancer-free when we traced the cases at 2.8 years after surgery. Even enlarged total parotidectomy allowed distant metastasis after surgery in the cases of preoperative facial nerve palsy. Therefore, it is conceivable that en-block extirpation including tumor, parotid gland, and facial nerve is appropriate for those cases to decrease the scattering of tumor cells during surgery. Further studies of diagnosis, surgical procedure, radiation therapy, and chemotherapy are needed to improve the prognosis of SDC.